PENINGKATAN MUTU GURU DALAM PROSES PEMBELAJARANMELALUI PENERAPAN SUPERVISI KUNJUNGAN KELAS DI TK BINAAN KOTA BENGKULU TAHUN PELAJARAN 2014-2015 - Nanik Irianwati (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2016)
One task is to carry out the supervision of Trustees at the school which they are responsible. To carry out effective supervision of classroom visits required conceptual skills, interpersonal and technical. Therefore, each supervisor should have mastered the concept of supervision and classroom visits that include: understanding, purpose and function, principles, and dimensions supervision substance class visit. One of the efforts made by supervisors in improving the quality of education is through improving the quality of teachers in teaching and learning is done through by supervisor coaching in classroom visits supervision. The purpose of this school action research was to determine the extent to which the implementation of supervision visits classes to improve the quality of teachers in the learning process in the city of Bengkulu Regional Patronage kindergarten school year 2014-2015. In action research was conducted in three cycles, the results of action taken proven to improve the quality of teachers to achieve the ideal standard. From 64.64% in Cycle I, can be increased to 76.07% in cycle II, and III cycle increased to 84.64%. School action research results showed that the application of the regulatory supervision of classroom visits can improve the quality of teachers to reach 100% completeness, the teachers are very positive response to the coaching is done by supervisor through classroom visits supervision.